Does Ukraine Need a Comprehensive Statute to “Control” Private Data Controllers? - Olena Dmytrenko; Cara D. Cutler (Washington University Global Studies Law Review, 2006)
This Article considers whether a European Union model of data protection, predominately in the form of a comprehensive statute, or a U.S. model of data protection, favoring industry self-regulation enhanced by sectoral legislation, would be best for Ukraine. This Article argues that a comprehensive statute may fit more easily into Ukraine's civil law culture and may prove to be a requirement necessary for the country to obtain its goal of accession to the European Union. However, until Ukraine builds a strong democratic legacy, a rapid transplant of the European Union-style comprehensive statute may be detrimental to nurturing nascent private businesses and independent media. The Article argues that Ukraine's short-term success demands adoption of a self-regulatory model akin to that of the United States for the time being. At the same time, slow steps should be taken to begin assessing whether or not implementation of a comprehensive statute in the future will suit Ukraine's long-term needs. Reprinted by permission of the publisher.
Keywords: Computers & amp; privacy; Computers – European Union countries; Privacy – European Union countries; Comparative law; Freedom of speech